Exploring the impact of natural language processing: a use-case of Chat GPT using sentiment analysis. - Khoo, Jia Yi (2024)

(untitled)
Artificial Intelligence (AI) has been widely used among the industry leaders. Its burgeoning increase of popularity has become a controversial topic among the public. In addition, AI has garnered public attention since the debut of generative AI, ChatGPT from OpenAI. ChatGPT has become viral since it was launched and available to the public. The rating and review of the app are being used as a reference and they are persuasive to the potential users. However, does rating and review has a positive relationship? This study will analyse how does review affecting ratings. Sentiment Analysis will be used in this research. This research has collected a sample of 2293reviews towards ChatGPT to examine the variables towards ratings. Data collected started from the introduction of ChatGPT Application on the IOS App Store until 26th July 2023. The outcome indicates that review have positive relationship towards rating. License was granted by creative commons.